The Usefulness of the Implementation of Environmental Management Systems Compliant with ISO 14001 for Environmental Insurance - Lemkowska, Malwina (Studia Oeconomica Posnaniensia, 2026)
usiness insurance is not a natural place to apply environmental management systems. Theoretical and empirical analyses do not show evidence - from the perspective of the insurer - of only advantageous changes in the level of claims, or in the ability to create useful information by entities that have implemented EMS. Moreover, in the present formal and legal context, it is not considered a good idea to reward the organization which obtained a certificate by offering lower premiums or more favourable insurance conditions. The activity of the insurance sector is essential to enhance the relationship between EMS and insurance. It is necessary to develop a set of critical factors of environmental risk underwriting and claims settlement procedures, which will be used for the preparation of guidelines, recommendations - for insurance purposes - directed towards ISO 14001 certification bodies, auditors, consulting firms and also organizations which are implementing environmental management systems. In view of the limited interest in environmental management amongst the insurers themselves, it is necessary to create an incentive for such actions by means of a macrosystem.